Students’ Communication Styles in Speaking Class at Universitas PGRI Sumatera Barat - Ikhsan, Muhammad Khairi; Siska, Siska; Yelliza, Yelliza (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is aimed at finding out the types of students’ communicatin styles in speaking class. In teaching and learning proccess, the students ofcourse have different communication styles. It depends on the students’ skill and readiness in performing their skill of communication in speaking class. This research, then belongs to descriptive with qualitative approach. The researcher used random sampling to determine the participants. There are 54 videos of the students’s speaking collected, meanwhile the researcher only takes 11 documents as the participants. The instruments of this research are video recordings and document checklists. There are three communication styles that the researcher concerned with, namely passive, aggessive, and assertive. From the research findings, it can be obviously stated that there are two communication styles found from the students’ speaking performace- they are passive and assertive. In brief, aggressive style is not found at all.